(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this paper, we have constructedpth associate class (p =5,7,…)is an odd numberincomplete block designs by establishing a link between PBIB designs and Latin square designs. Illustration of construction of such type of designs are also discussed in detail. Efficiencies of the newly constructed PBIB designs are also computed for the purpose of comparison. During the study, it was found that some designs are new and some newly constructed are more efficient as compared to the existing designs.